2016
DOI: 10.3109/17453674.2016.1152853
|View full text |Cite
|
Sign up to set email alerts
|

Osteolytic changes around biodegradable cement restrictors in hip surgery

Abstract: Background and purposeBiodegradable cement restrictors are widely used in hip arthroplasty. Like others, we observed osteolytic reactions associated with a specific cement restrictor (SynPlug; made of PolyActive) and reviewed our patients.Patients and methodsWe identified 703 patients with suitable radiographs from our database (2007 to 2012) who underwent cemented hip arthroplasty and received a SynPlug biodegradable cement restrictor. We reviewed all available radiographs to determine the incidence, severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…1 study found an average increase in cortical ratio as a measure of osteolysis of 14% after an average 1.8 year follow-up. 12 Another found that 87% had >10% cortical thinning after 1 year. 10 Both studies had a rather short follow-up and did not compare the PEG/PBT restrictor with other cement restrictors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 study found an average increase in cortical ratio as a measure of osteolysis of 14% after an average 1.8 year follow-up. 12 Another found that 87% had >10% cortical thinning after 1 year. 10 Both studies had a rather short follow-up and did not compare the PEG/PBT restrictor with other cement restrictors.…”
Section: Resultsmentioning
confidence: 99%
“…We assumed that the plug was located immediately underneath the inferior border of the cement mantle (Figure 1). 12 The cortical ratio was assessed on radiographs of the 1st postoperative day (T0) and at follow-up.…”
Section: Measurement Of the Cortical Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…In cemented femoral components, intramedullary plugs are commonly used and are available in a wide variety of materials and shapes, both biodegradable and non-resorbable. Osteolytic changes around biodegradable models have even been described [ 46 ]. Some types of restrictors have a metallic marker that can appear at the tip of the stem ( Figure 1 ).…”
Section: Types Of Hamentioning
confidence: 99%